A Study on Dredged Sea Sand as an Optimum Replacement for Fine Aggregate in Concrete - R. Manigandan; Srinivasan, V.; Pazhani, K. C. (Asian Journal of Engineering and Applied Technology, 2018)
This paper deals with the study and feasibility on utilization of dredged sea sand by conducting various experiments on physical properties like sieve analysis, gap grading. Chemical properties like percentage of organic content, chloride content, sulfur content, presence of deleterious material and volatile solids in dredged sea sand have been determined. The experiments like rapid chloride penetration test, water absorption test, alkalinity test, accelerated corrosion test, sulphur resistance test, acid resistance test, and sorptivity. Durability and strength of concrete have been studied by considering various properties of fine aggregate. The mix design have been done for M30 grade of concrete and the percentage of replacements 25%, 50%, 75%, and 100% of M-Sand (Manufacture Sand) of concrete specimen for all the experiments is considered. As we all know our current scenario of increase in demand of fine aggregate leads to scarcity of river sand. This has increased in research on dredged sea sand as a fine aggregate in concrete to reduce the demand on fine aggregate in construction industries. Comparative study of M-sand, river sand and dredged sea sand has been done. The dredged sand which is used for the study and testing is dredged to increase the sea bed depth of Ennor port for the accessibility of mother ship, it was collected from the coastal areas of Ennore Port (Kamarajar Port) and subjected to rain, and atmospheric conditions for a year.